Severe Acute Respiratory Syndrome by COVID-19: Clinical- Epidemiological Profile and Spatial Distribution of Deaths in the States of Brazil - Alves de Oliveira, Rayanne; Santos Neto, Marcelino; Maia Pascoal, Lívia; Miranda Bezerra, Janaína; Stabnow Santos, Floriacy; dos Santos Brito, Paula; da Silva de Sousa, Giana Gislanne (O Mundo da Saúde, 2022)
Severe Acute Respiratory Syndrome (SARS) is a severe manifestation of COVID-19 infection that, in some cases, can result in death. In the current global epidemiological scenario, Brazil is the second country with highest number of deaths from the disease; thus, it is necessary to know the clinical and epidemiological characteristics of deaths and how they are spatially distributed across territories. Therefore, the objective was to describe the clinical and epidemiological characteristics and the spatial distribution of SARS deaths due to COVID-19 in the Brazilian federative units (states). This is a descriptive and ecological study of SARS deaths due to COVID-19 in Brazilian states, from March 2020 to June 2021, based on secondary data available on the openDataSUS database. Descriptive statistics were performed for the clinical-epidemiological variables and the monthly mortality rates were determined by state and thematic maps were made in QGIS software version 2.4.17. A total of 196,109 deaths were recorded in the investigated period, predominantly male, older, white, and low-educated. Among the clinical variables, cough, respiratory distress, dyspnea, and the presence of comorbidities stood out. A heterogeneous spatial distribution of deaths was observed, with rates ranging from 0.00 to 24.59 deaths/100,000 inhabitants, the highest rates were in the states of Rio de Janeiro, Amazonas, Ceara, Sergipe, Sao Paulo, and Pernambuco. These findings raise the need for investments on the part of public management and health systems and services in the most affected states, improvements in epidemiological surveillance, permanent health education, increased access to immunization and health prevention measures to control and monitor SARS caused by COVID-19.